Efficacy of the antagonistic fungus Talaromyces tratensis KUFA 0091 in controlling rice blast and brown leaf spot diseases in field trials - Dethoup, Tida; Jantasorn, Arom; Kaewsalong, Nipon (Agriculture and Natural Resources, 2022)
Importance of the work: Rice blast and brown leaf spot are the most devastating foliar diseases in rice production in Thailand and many countries. Objectives: To evaluate the efficacy of Talaromyces tratensis KUFA 0091 to control rice diseases. Materials & Methods: The efficacy was evaluated of a spore suspension (1×106 spores/mL) and a crude extract of KUFA 0091 at 1 g/L, 5 g/L and 10 g/L at the time of application, with one or two applications to control rice blast and brown leaf spot diseases in two susceptible rice varieties. Results: There was no significant difference between the means of two and one applications in controlling both diseases. However, spore suspension (1×106 spores/mL) and the crude extract (5 g/L of T. tratensis KUFA 0091) were the most effective in controlling brown leaf spot, with disease reduction in the field of 52.47% and 45.04%, respectively, when applied twice. The spore suspension and the crude extract (at 1×10 g/L of T. tratensis KUFA 0091) were moderately effective against rice blast, reducing its incidence by 35.83% and 35.11%, respectively, when applied twice under field conditions. Main finding: There was antagonistic activity of T. tratensis KUFA 0091 via antibiosis against rice pathogens, as it produced substances absorbed by the rice plant, which then moved to newly emerging leaves, protecting them from pathogen infection.